Physicochemical profiles of honey harvested from four major species of stingless bee (Kelulut) in North East Peninsular of Malaysia - Syafizal Omar; Francis Kanyan Enchang; Mohd Ulul Ilmie Ahmad Nazri; Mohd Mansor Ismail; Wan Iryani Wan Ismail (Penerbit Universiti Kebangsaan Malaysia, 2019)
Stingless bee honey is one of the high demand honey in Malaysia. However, honey characters particularly from different species is lacking in order to increase its commercial value. Thus, physicochemical profile analysis of honey harvested from four major species of stingless bee in Kelantan, Malaysia, Geniotrigona thoracica, Heterotrigina itama, Lepidotrigona terminata and Tetragonula laeviceps was conducted to investigate the honey character. Character of the stingless bee honey harvested from various species from the same geographic area was compared. The results were then compared to stingless bee honey from other countries. Most of physicochemical data of stingless bee honey from different species collected from Kelantan showed almost similar values. However, value of pH, free acidity and total acidity displayed significant different results. This indicates species of stingless bee may affect the results. In order to compare local stingless bee honey with international stingless bee honey, the data was represented as mean regardless of their species. From the results, moisture content was consistently high in stingless bee honey harvested from Malaysia, Thailand, Brazil and Venezuela while, other data showed different values. The results demonstrated that species of stingless bee particularly from other countries is crucial in order to characterize the honey. However, Malaysian stingless bee honey has unique character based on physicochemical data. The data can be used as a marketing strategy in increasing commercial value of local stingless bee honey.